2014
DOI: 10.3402/qhw.v9.24255
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the communication between telenurse and caller—A critical discourse analysis

Abstract: BackgroundTelenursing is an expanding service in most Western societies. Sweden is a front-line country, with all of its 21 counties connected to Swedish Healthcare Direct (SHD) 1177. The intention of the service is twofold: to make health care more efficient, while also making it more accessible and safe for patients. Previous research has shown, however, that the service is not used equitably. Gender, age, socio-economic, and ethnicity differences have been reported as determining factors for the use of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 32 publications
2
35
0
Order By: Relevance
“…In line with the findings from the UK (Knowles et al ), SHD was difficult to use for patients with language problems (Hakimnia et al ). Knowles et al () conclude that TN could be problematic if some groups in the population are less likely to use it.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…In line with the findings from the UK (Knowles et al ), SHD was difficult to use for patients with language problems (Hakimnia et al ). Knowles et al () conclude that TN could be problematic if some groups in the population are less likely to use it.…”
Section: Discussionsupporting
confidence: 71%
“…The remaining articles on communication covered gender and cultural constructions in dialogues. Hakimnia et al () identified five types of calls, which were grouped under three wider themes: a gatekeeping theme, a medicine‐focused theme, and a theme concerning gender. In gatekeeping calls, the focus was on directing callers to the appropriate level of care.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[11] The societal gender order has also been shown to be mirrored in calls to SHD, as representations of the reluctant male caller and the ideal feminine caller were identified by discourse analysis of authentic calls. [24] As for the actual calls, the mean call length in the whole study sample was 4 minutes and 30 seconds. For men, the mean call length was 4 minutes, and for women 4 minutes and 40 seconds, as previously mentioned.…”
Section: Discussionmentioning
confidence: 99%